Percutaneous Transhepatic Laser Lithotripsy for Biliary Stones in Patients with Altered Biliary Anatomy - Indu, Jacob; Kheda, Vikrama Amitha; Bolbandi, Deepak; Govil, Sanjay; Bhat, Ravisankar (Journal of Clinical Interventional Radiology ISVIR, 2021)
Endoscopic retrograde cholangiopancreatography (ERCP) is the current treatment of choice in bile duct stones. Several factors such as variant anatomy of ampulla and surgical procedures like hepaticojejunostomy limit the success of ERCP in treating bile duct stones. Percutaneous transhepatic laser lithotripsy using interventional radiologic and endourologic techniques, which is uncommon, is a reasonable treatment option in such difficult cases. It is a minimally invasive, safe procedure accompanied by a high success rate, minimal morbidity, and a short hospital stay. We report our technique and experience in a series of three patients who underwent percutaneous transhepatic biliary drainage (PTBD) followed by percutaneous transhepatic laser lithotripsy in an attempt to avoid open surgery when ERCP was technically difficult.
Keywords: percutaneous lithotripsy; biliary stones; holmium laser